ASEAN in Digital Economy: Opportunities and Challenges - Avirutha, Anupong Avirutha (Journal of ASEAN PLUS Studies, 2021)
Abstract Developing countries like most countries in Southeast Asia have the opportunity to transform its economy and to contribute to the development of the digital economy. Although these economies are characterized by high added value, faced with numerous obstacles, many developing countries cannot adequately respond to the demands of the digital economy. The problems and challenges faced on the road to becoming digital and analyses a new approach for business industries to initialize their digital transformation. The objective of this article is to review the opportunities and challenges that ASEAN countries have to face to initialize their digital transformation. The digitalization of a growing number of new business opportunities, including new types of products and services goods is huge access to crowd-sourced. On the other hands, the problems and challenges are the inadequate access to the latest technology, sophisticated telecommunications infrastructure, low computer literacy as well as numerous cultural and socio-economic.